Pengaruh Motivasi Belajar, Sarana dan Prasarana dan Lingkungan Keluarga terhadap Kemandirian Belajar dengan Efikasi Diri sebagai Variabel Mediasi - Anggraini, Shinta Dewi; Tusyanah, Tusyanah (Universitas Negeri Semarang, 2023)
The purpose of this study was to examine the influence of learning motivation, facilities and infrastructure, and the family environment on learning independence with self-efficacy as a mediating variable. The type of research used in this research is quantitative. Data was collected by questionnaire and analyzed using SEM-PLS. The population in this study were 134 students majoring in office administration education at UNNES in 2022. The sampling technique uses a saturated sample technique with descriptive analysis and inferential analysis methods. The results showed that of the 7 (seven) hypotheses proposed, there were 2 (two) hypotheses that were rejected and 5 (five) hypotheses accepted, with the following details, learning motivation has a positive and significant effect on learning independence, as well as learning motivation mediated by self-efficacy has a positive and not significant effect, facilities and infrastructure have a positive and significant effect on learning independence, facilities and infrastructure mediated by self-efficacy have a positive and significant effect, family environment has a positive and significant effect on learning independence, environment family mediated self-efficacy has a positive and significant effect. Furthermore, self-efficacy has a positive and not significant effect on learning independence.